METHODICAL APPROACH TO RISK MANAGEMENT IN A MANUFACTURING ENTERPRISE - Mukhitdinov Shukhrat Zivitdinovich (Journal Park Publishing, 2024)
In the article, the methodologies of factors in improving the methodological foundations of improving the effectiveness of Management in production enterprises are taken according to the modern approach of taxing. Also developed proposals and recommendations for integration of risk management into management processes by providing an algotirim of Enterprise Risk Management and an Enterprise Risk System.
Keywords: risk, production, management, methodology and integrations.